63 Effect of Preload Reduction on Left Ventricular Torsion in Patients with Heart Failure and Preserved Ejection Fraction on Maintenance Haemodialysis. (31st May 2014) - Lee, Eveline; Fraser, Alan; Yousef, Zaheer
Abstract : Background: The effects of dialysis on diastolic flow, short and long axis function have been previously studied. However its effect on left ventricle (LV) rotation and torsion is not known. LV rotation and torsion contribute significantly to overall LV function and can be assessed non-invasively with 2 dimensional speckled tracking on standard echocardiography short axis images. We investigated the effect of preload reduction on LV rotational mechanics following a single session of haemodialysis. Methods: Thirty subjects (Age 59 ± 18 years, LVEF 64 ± 6%, LVEDVI 38 ± 14, LVMI 119 ± 62) on maintenance haemodialysis (median duration 26 months) with symptoms of heart failure and preserved ejection (NYHA class II) consented to take part in the study. Standard echocardiography were performed immediately before and after a mid week session of haemodialysis (mean duration 4 h). Images were acquired and analysed offline using dedicated software, Echopac. All data were explored for normality. Continuous variables were reported as mean ± standard deviation (for normally distributed data) or median (for skewed distribution); categorical data were reported as percentages. Statistical analyses were performed using SPSS 20, paired t-test or Wilcoxon sign-rank test was used for paired comparison before and after dialysis. A 2-tail p value of <0.05 was considered significant. Results: Majority of subjects had hypertension (93%, blood pressure 131 ± 25/68 ± 16 mmHg) and some had diabetes mellitus (30%) and non flow limiting coronary artery disease (13%, CCS class I). Causes of renal failure were hypertension (63%), obstructive uropathy (27%) and diabetes mellitus (20%). Use of cardiovascular medication was beta blocker (23%), diuretics (23%), ACE inhibitor (16%), doxazosin (10%) and calcium channel blocker (1%). The median weight loss following dialysis was 1.6 ± 1.3 kg (95% CI 1.1–2.1, p < 0.001). Table 1 show the results using 2 dimensional speckled tracking echocardiography. Conclusion: Preload reduction resulted in increased apex rotation and overall LV torsion, despite unchanged early untwisting and peak untwisting rate. These findings suggest unchanged intrinsic myocardial properties despite a positive inotropic response.